1995
DOI: 10.1055/s-2007-972984
|View full text |Cite
|
Sign up to set email alerts
|

Serum Amino Acid Concentrations in Nine Athletes Before and After the 1993 Colmar Ultra Triathlon

Abstract: The amino acid imbalance hypothesis should explain the fatigue originating in the brain during sustained exercise or over-training as a branched-chain (BCAA)/aromatic amino acids (AAA) imbalance with increased brain tryptophan uptake and 5-hydroxytryptamine synthesis. The serum amino acid profile was determined in 9 ultra-triathletes before and after completing the 1993 Colmar ultra-triathlon to additionally analyse the extent of this amino acid imbalance during such an extreme prolonged contest lasting more t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
2

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(82 citation statements)
references
References 5 publications
4
72
0
2
Order By: Relevance
“…Decreases in plasma glutamine levels by intense and prolonged exercise and physical stress were demonstrated in several previous studies [61][62][63][64][65] . Also, it was reported that plasma glutamine levels were lower in athletes with "overtraining syndrome", caused by intense long-term training and associated stress, than in those who were not in a state of overtraining 66,67) .…”
Section: Taurinementioning
confidence: 89%
“…Decreases in plasma glutamine levels by intense and prolonged exercise and physical stress were demonstrated in several previous studies [61][62][63][64][65] . Also, it was reported that plasma glutamine levels were lower in athletes with "overtraining syndrome", caused by intense long-term training and associated stress, than in those who were not in a state of overtraining 66,67) .…”
Section: Taurinementioning
confidence: 89%
“…Second, the growth defect of the serC mutant in minimal medium does not appear to be a generalized effect but is instead largely specific to early phase and can be completely restored by the addition of exogenous serine. Third, chemical analysis of human serum suggests that the levels of exogenous free serine in human serum are unlikely to be limiting for serC mutant growth (19,29). For these reasons, we currently favor the regulatory model, which posits that serC may not simply act as a general housekeeping gene but may also be involved in the synthesis of components specifically required for B. pseudomallei virulence.…”
Section: Discussionmentioning
confidence: 99%
“…Frequent intense exercise and training has been shown to impair the immune response and might increase the susceptibility to infections (Castell and Newsholme, 1996). Some authors explain the increase in susceptibility to infections due to a decrease in plasma glutamine concentration, which impairs some neutrophil functions (Smith and Wilmore, 1990;Parry-Billings et al, 1992;Keast et al, 1995;Lehmann et al, 1995;Pedersen and Hoffman-Goetz, 2000). In support of this hypothesis, Nieman (1997) showed that glutamine supplementation decreased upper respiratory tract infections in athletes.…”
Section: Cell Defense and Repairmentioning
confidence: 98%